Introduction The History of Education: Jesuits and Schooling - Bieś, Andrzej Paweł; Topij-Stempińska, Beata (Studia Paedagogica Ignatiana, 2019)
The 80th birthday of Fr. Prof. Ludwik Grzebień SJ—a Jesuit, historian and researcher of the history of the Jesuit Order in Poland—was the inspiration for the preparation and publication of the 4th issue of Studia Paedagogica Ignatiana on the history of the Jesuits and their educational activity. Until now, the Professor has published almost 1400 texts, which include “the history of African missionaries and a text about the pastoral ministry among the Polish immigrants in America at the turn of the 19th and 20th centuries, works about Khyriv (…), about Jesuit schools and the WAM Publishing House, [and] about Jesuits in Lviv, Toruń, Pułtusk, Kraków, and Sandomierz” (Terlecki 2010: 21), as well as a two-volume bibliography of the history of the Society of Jesus in Poland. The newest of his books include The Inventory of the Southern Province of the Society of Jesus in Kraków. Manuscripts up to 1820. Apart from those historical images, editions of sources, biographies and bibliographies, lexicons, and other tools supporting the future generations of researchers in developing their scientific skills, we have to add local monographs, such as his history of Dobrzechów or of the parish in Strzyżów. This is because Prof. Ludwik Grzebień is the “master of details, historical features, little things that constitute the monument of the past ages” (Terlecki 2010: 21). In order to celebrate the above-mentioned anniversary in the proper manner, the editorial board invited a group of foreign researchers whose scientific activity and published works are connected with restoring the history of the Society of Jesus and developing the knowledge of Jesuit education.